INTEGRATION ISLAMIC VALUES IN DEVELOPING MATERIAL TROUGH FLIP BOOK AT HIGHER EDUCATION - Syamsiah Depalina Siregar; Tinur Rahmawati Harahap; Farida Hanim Saragih; Anggraini Thesisia Saragih (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
This study was aimed at describing the integration of Islamic values in the process of learning at Higher Education. This research focus was on developing material trough Flip book which integrated Islamic values in higher education. The study was research development. This study aimed to develop learning material that was suitable for use in higher education trough flip book for higher education. This research is classified as Research and Development (RD) research with ADDIE procedures consisting of Analysis, Design, Development, Implementation and Evaluation. This research was limited to the development stage. The results of this research were performed as follows. First, the integration of Islamic values and lesson plans were done in the sections of instructional objectives and in the instructional materials. Second, the integration of Islamic values and material developments were done through several ways such as: (a) adding the exercise reflecting the Islamic values to the topic presented, (b) modifying the Islamic names of people, place and events (c) embedding the verses Al-Qur’an to the suitable materials (d) mixing Islamic expressions and the relevant English expressions with the main materials. Third, the integration of Islamic values and the English teaching learning activities were: (a) by conducting code mixing and code switching between English and the Islamic expressions, (b) linking to the topic discussed to the verses of Al-Qur’an, (c) using Islamic names for people.